ANALYSIS OF STUDENTS' UNDERSTANDING OF MATHEMATICAL CONCEPTS ON FRACTIONS IN GRADE VIII AT SMP NEGERI 2 MAZINO - Luaha, Aldin (Afore : Jurnal Pendidikan Matematika, 2024)
This study aims to describe and identify the factors contributing to the low understanding of mathematical concepts related to fractions among students. This research is qualitative in nature with a descriptive approach. The informants in this study are 18 eighth-grade students from SMP Negeri 2 Mazino. Data were analyzed through the steps of data reduction, data presentation, and conclusion drawing. The data collection techniques used are tests and interviews. The results show that, overall, students exhibit low understanding of concepts when distinguishing between two fractions, with 18% categorized as very poor. In classifying fractions by type, the percentage is 19% in the very poor category. For ordering fractions from smallest to largest, the percentage is 37%, categorized as poor. In simplifying addition and subtraction operations involving fractions, 22% fall into the poor category. Additionally, in relating everyday life to fraction concepts, the percentage is 60%, categorized as sufficient, while 20% fall into the very poor category. Factors influencing this include a lack of understanding of the statements in the tests, not comprehending the questions posed, being less meticulous in understanding simple fractions, and difficulty in interpreting word problems related to fraction operations. In conclusion, eighth-grade students at SMP Negeri 2 Mazino demonstrate low understanding in completing tests on fractions. It is recommended that teachers create a question-and-answer space in their lesson plans to enhance students' conceptual understanding when working with fractions.